A qualitative exploration of evidence-based decision making in public health practice and policy: the perceived usefulness of a diabetes economic model for decision makers. (1st November 2019) - Grove, Amy; Sanders, Tom; Salway, Sarah; Goyder, Elizabeth; Hampshaw, Susan
Abstract : Purpose The purpose of this paper is to explore the perceived usefulness of a diabetes economic model as a potential tool for aiding evidence-based decision making in public health. Methods Fifteen interviews and two focus groups, with four participants in each, were conducted with health and management professionals working in one public health department in a local council. Data were analysed using inductive thematic analysis to generate four themes. Findings The findings reflect attitudes and beliefs of a diverse staff group situated in public health services. Findings reveal that the economic model was perceived as useful and participants reported positive views regarding the principles of economic modelling for decision making. However, it was potentially problematic in practice due to organisational constraints linked to limited resources, restricted budgets and local priorities. Differences in institutional logics of staff working across public health and local government departments were identified as a potential barrier to the use of the model in practice. Discussion The findings highlight anticipated challenges that public health practice and policy decision-makers could face if they selected to implement an economic modelling approach to fulfil their evidence needs. Previous studies have revealed that healthcare decision makers would find evidence around the economic impacts of public health interventions useful, but this information was not always available in the format required. This paper provides insights into how public health staff perceive economic modelling, and explores how they use this type of evidence when making public health practice and policy decisions.